Programming your home : automate with Arduino, Android, and your computer - Riley, Mike (Computer scientist) (Pragmatic programmers., 2012)
In Programming Your Home, technology enthusiast Mike Riley walks you through a variety of custom home automation projects, ranging from a phone application that alerts you to package deliveries at your front door to an electronic guard dog that will prevent unwanted visitors.--